Marketing Strategies And Performance Of Indigenous Construction Firms In Nigeria - Ogbu, *Chukwuemeka Patrick (Penerbit Universiti Sains Malaysia, 2017)
Despite increased competition, construction firms are generally known to be lagging in the adoption of marketing strategies. The performance of indigenous construction firms (ICFs) in Nigeria has been severally criticised without commensurate research efforts to address the problem. This study focused on the influence of marketing strategies on the performance levels of ICFs in South-South Nigeria. Study questionnaires were purposively issued to CEOs and managers of ICFs (n = 87) in the research area. Maintaining a pool of professionals to boost company image ( x = 3.79) ranks highest among the identified marketing strategies. The Kruskal-Wallis H test of difference in the opinions of the different firm groups showed that a significant difference exists in the frequency of use of the marketing strategies by the different firm groups. A significant difference (p = 0.013) exists in the frequency of use of the marketing strategies by average performers (mean rank = 57.84) and high performers (mean rank = 78.03). The groups of marketing strategies that influence ICF level of performance are third-party-based, client-based, firm-based, and publicity-based strategies. Average-performer ICFs should make more frequent use of marketing strategies, and the use of project performance-based marketing strategies by ICFs should be increased